THE PATTERNS OF ISLAMIC EDUCATION DURING THE TIME OF THE PROPHET MUHAMMAD - Mokodenseho, Sabil; Rohmah, Siti; Idris, Muh; Aziz, Adit Mohammad; Rahman, Rahman (Institut Agama Islam Negeri (IAIN) Manado, 2024)
Penelitian ini bertujuan untuk menganalisis pola pendidikan Islam pada masa Nabi Muhammad SAW. Kajian ini menjadi penting karena pendidikan Islam mempunyai arti penting bagi umat Islam dalam meneladani proses pendidikan Islam sejak zaman Nabi, yang bermanfaat untuk memahami pertumbuhan dan perkembangan pendidikan Islam, sehingga mampu menjawab persoalan-persoalan kontemporer dalam pendidikan Islam. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan deskriptif. Data mengenai sejarah pendidikan Islam pada masa Nabi Muhammad diperoleh melalui pembacaan dan kajian mendalam terhadap berbagai literatur. Penelitian ini menemukan pendidikan Islam di masa Rasulullah telah berlangsung di Mekah dan Madinah. Di Mekah, Nabi menjadikan lembaga pendidikan, yakni rumah, Dar al-Arqam dan Kuttab sebagai sarana yang efektif dan efisien. Materi pendidikan Islam berisi pendidikan akhlak dan budi pekerti, dan pendidikan jasmani (kesehatan), seperti menunggang kuda, memanah, dan menjaga kebersihan. Sementara pola pendidikan yang diterapkan Nabi di Madinah berorientasi pada pemantapan nilai-nilai persaudaraan antara kaum Muhajirin dan Anshar. Nabi mendirikan masjid dan Suffah sebagai sarana yang efektif. Muatan pendidikannya menekankan pada penanaman tauhid, pendidikan keluarga, pendidikan masyarakat, dan budi pekerti. Semua ini efektif karena motivasi dari dalam masyarakat Madinah dan karisma serta metode yang digunakan Nabi dalam menangani kepentingan masyarakat secara adil dan demokratis. Temuan ini menunjukkan pola pendidikan Islam yang diterapkan Nabi Muhammad SAW. di Mekah dan Madina. Kesimpulannya, pendidikan Islam dalam sejarahnya telah berkontribusi besar terhadap peradaban manusia terutama umat Muslim di dunia. This research aims to analyze the patterns of Islamic education during the time of the Prophet Muhammad. This study is important as Islamic education holds significance for Muslims in emulating the process of Islamic education since the time of the Prophet, which is beneficial for understanding the growth and development of Islamic education, thus addressing contemporary issues in Islamic education. The research methodology employed is qualitative with a descriptive approach. Data regarding the history of Islamic education during the time of the Prophet Muhammad was obtained through extensive reading and study of various literature sources. The study finds that Islamic education during the Prophet occurred in Mecca and Medina. In Mecca, the Prophet established educational institutions, such as homes, Dar al-Arqam and Kuttab as effective and efficient means. The curriculum of Islamic education included moral and character education, as well as physical education (health), such as horse riding, archery, and hygiene. Meanwhile, the educational pattern implemented by the Prophet in Medina focused on strengthening the values of brotherhood between the Muhajirin and the Ansar. The Prophet established mosques and Suffah as effective means. The educational content emphasized the cultivation of monotheism, family education, community education, and manners. All of these were effective due to the motivation from within the Medina community and the charisma and methods employed by the Prophet in fairly and democratically addressing the community's interests. These findings illustrate the pattern of Islamic education implemented by the Prophet Muhammad in Mecca and Medina. In conclusion, throughout history, Islamic education has significantly contributed to human civilization, particularly for the Muslim community worldwide